Intersection between Andragogy and Transformative Learning - Somanita Kheang (Adult Education Research Conference, 2019)
The intersections between andragogy and transformative learning were observed through three lens: application of andragogy and transformative learning in classroom, spirituality, and various contexts where learning is a multi-dimensional phenomenon.
Keywords: Intersection; Andragogy; Transformative Learning; Adult Learning; Spirituality